The Art Deco style : in household objects, architecture, sculpture, graphics, jewelry ; 468 authentic examples (New York : Dover Publication, Inc., 1972)
Art Deco gardens and terraces...Art Deco dwellings (including the Bauhaus faculty residences designed by Walter Gropius)... Art Deco interiors...Art Deco furniture (with chairs by Le Corbusier, Marcel Breuer, and P. Jeanneret)... Art Deco metalwork (the elevator shaft of the Grunfeld Department Store, lighting fixtures, lettering, locks and folding screens)...
Terraces and gardens -- Dwellings -- Interiors -- Interior details -- Furniture -- Metalwork -- Large buildings -- Rugs and fabrics -- Shops and department stores -- Bindings -- Art objects -- Advertising -- Stained glass -- Sculpture -- Everyday objects -- Jewelry -- Ornamental sculpture -- Index
Keywords: ART DECO